Metabolomics biomarker analysis of threatened abortion in polycystic ovary syndrome: a clinical discovery study. Issue 83 (15th November 2017) - Feng, Xiaoling; Chen, Lu; Li, Na; Zhao, Yan; Han, Qimao; Wang, Xiaolin; Wang, Wei; Ma, Liping; Zhao, Xinjie
Abstract : In this study, using an advanced metabolomics platform based on UPLC-QTOF-MS, we found that pregnancy significantly altered the profile of metabolites in the plasma of women with PCOS. Abstract : Metabolomics is the comprehensive assessment of endogenous metabolites of a biological system in a holistic context. Threatened abortion in polycystic ovary syndrome (PCOS) is a heterogeneous disorder with a miscarriage rate of up to 30–50% in women. However, metabolic changes regulated by threatened abortion in women with polycystic ovary syndrome are not clearly understood. Current pregnancy screening tools to identify women with PCOS that are at risk of threatened abortion lack both specificity and sensitivity. In this study, using an advanced metabolomics platform based on ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS), we found that pregnancy significantly altered the profile of metabolites in the plasma of women with PCOS. Mothers with PCOS and healthy controls could be clustered into two distinct groups based on multivariate statistical analysis. The current metabolomics approach based on UPLC-QTOF-MS indicated 7 ions (6 in the positive mode and 1 in the negative mode) as differentiating metabolites which, to some extent, contribute to the progress of threatened abortion. All these different metabolites led to abnormalities of the fatty acids, lipid metabolism and beta-oxidation of fatty acids in mothers with PCOS. This study was designed to explore the holistic metabolomic profile of threatened abortion as a result of PCOS. To our knowledge, this work is the first report using a metabolomic approach to propose metabolic changes in plasma in the threatened abortion of women with PCOS. Thus, our method is an efficient procedure for the pathogenesis of threatened abortion with mothers with PCOS.